Col@b formacional com as culturas digitais : tecendo redes docentes interativas e colaborativas - Santos, Sandra Virginia Correia de Andrade (2021)
In the context of digital cultures, teacher training still persists in the view of training "for the use of", with specific and standardized processes, marking a conception of training centered on the immediate domain of the devices. Based on this, this thesis is based on the understanding that, in order to weave new know-how, it is necessary to create, at school, formational spacetime, in which teachers find themselves involved with their realities and in a process of dialogue and reflection with technologies as cultural artifacts. This understanding raised the following research questions: How do teachers experience digital cultures in formational spaces that are open to the emergences of their daily lives? How and which know-doings are mobilized and/or (re)created? What potentialities emerge in these formational spaces? Facing these provocations, this study aimed to understand the formational spacetimes with digital cultures open to the happening, trying to understand how the formation is woven when it opens to their problems, their ideas, their needs, dilemmas and possibilities. For the weaving of this study, I took as my basis theoretical references that contributed to the discussion of an open training to the daily life of teachers, even trying to break with the classical view of science, given the multiplicity of the phenomenon studied. Thus, the theoretical-methodological approach chosen was research-training, a perspective based on the immersion and reflection of both the subject and the researcher themselves, whose gaze takes place in two directions. In tune with this, I immersed myself in the epistemological assumptions of complexity, multireferentiality, and everyday life, in dialogue with digital cultures and teacher education. This study was carried out in a public school in the municipality of Tobias Barreto, in the state of Sergipe, and had the co-authorship of 16 elementary school Portuguese Language teachers. In its weaving, we created the Col@b Formacional, a formative device created together with the itinerancy appdiaries and the mediated com-versation. After all this immersion and the experiences lived together with the teachers, three subsuming notions emerged, which I consider the findings and meanings of the research: spacetime of multireferential com-versations; teacher networks of collaboration and co-creation and formative weaving of the acts of curriculum, the latter unfolded in experiential and creative narratives; and plural authorship and citizen formation. In this sense, I infer that the training of teachers in action and situated in the context of digital cultures when open to the emergence of the daily teaching potentiates interactivity and collaboration, enabling the co-creation of curriculum acts loaded with multiple possibilities for learning-teaching. This movement lived and experienced in the research points to a perspective of training that can re-signify teaching practices with digital technologies, referenced in an exercise implicated with its own contexts, in a flexible, open and inventive perspective.